2017
DOI: 10.3233/jin-170056
|View full text |Cite
|
Sign up to set email alerts
|

QEEG-based neural correlates of decision making in a well-trained eight year-old chess player

Abstract: The neurocognitive substrates of decision making (DM) in the context of chess has appealed to researchers' interest for decades. Expert and beginner chess players are hypothesized to employ different brain functional networks when involved in episodes of critical DM upon chess. Cognitive capacities including, but not restricted to pattern recognition, visuospatial search, reasoning, planning and DM are perhaps the key determinants of rewarding and judgmental decisions in chess. Meanwhile, the precise neural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The present research focuses on explaining neurocognitive disorders from the point of view of microgenetic theory using modern neurotechnology, such as quantitative electroencephalography (QEEG) and event-related potentials (Alipour, Seifzadeh, Aligholi et al 2017;Pąchalska, Kaczmarek & Kropotov 2014;Pąchalska, Góral -Półrola, Mueller et al 2017;Sowndhararajan, Kim, Deepa et al 2018). Results from QEEG point to the presence of neuronal correlates of the clinical image of disorders in children with epilepsy (Ouyang, Chiang, Yang et al 2018;Lin, Ouyang, Chiang et al 2014), ADHD (Kropotov, Grin-Yatsenko, Ponoma rev et al 2005;Tye, Asherson, Ashwood et al, 2014), and ASD syndrome (Kozhush ko, Nagornova, Evdokimov et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The present research focuses on explaining neurocognitive disorders from the point of view of microgenetic theory using modern neurotechnology, such as quantitative electroencephalography (QEEG) and event-related potentials (Alipour, Seifzadeh, Aligholi et al 2017;Pąchalska, Kaczmarek & Kropotov 2014;Pąchalska, Góral -Półrola, Mueller et al 2017;Sowndhararajan, Kim, Deepa et al 2018). Results from QEEG point to the presence of neuronal correlates of the clinical image of disorders in children with epilepsy (Ouyang, Chiang, Yang et al 2018;Lin, Ouyang, Chiang et al 2014), ADHD (Kropotov, Grin-Yatsenko, Ponoma rev et al 2005;Tye, Asherson, Ashwood et al, 2014), and ASD syndrome (Kozhush ko, Nagornova, Evdokimov et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Alipour et al published a case report on the use of quantitative electroencephalography in an eight-year-old boy with substantial chess training while he was playing chess against a computer. The authors observed a lower power spectral density in higher frequency bands in the right hemisphere in decision making during the game 30 .…”
Section: Chess and Cognitive Functionmentioning
confidence: 91%